Peningkatan Kualitas Masyarakat Dalam Penanggulangan Bencana Non Fisik (Stunting) Melalui Pelatihan Manajemen Stunting Pada Rumah Desa Sehat (RDS) Desa Suci - Zuhrotul Eka Yulis Anggraeni; Ely Rahmatika Nugrahani; Marethe Rezanastya; Nadya Intifadha Furensa (Indonesian Journal Publisher, 2023)
Stunting management is a method developed with a community-based approach. The management of stunting begins with increasing related knowledge about stunting to forming family companions with stunting. The mentoring process is carried out comprehensively and from all levels of society. The method used in this trial was to increase knowledge of the RDS (Healthy Village House) and the cadres of the Suci village posyandu. The results of the dedication were knowledge binding related to stunting management at RDS and posyandu cadres. Knowledge related to stunting management, especially the problem of family companions, is the basic capital for Posyandu cadres in applying assistance to stunting families.